Entrance porch, Fairlawn - Ghosh, Ayan (Jio Institute, 2023)
Fairlawn, 128 Maharshi Karve Road, Churchgate. The Art Deco buildings in Mumbai were mostly designed by a small group of Indian and British architects. They had studied architecture in the West and returned to India with accreditation from the Associates of the Royal Institute of British Architects (ARIBA).